Subacute effusive-constrictive pericarditis in a patient with COVID-19 - Diaconu, Rodica (BMJ Case Rep, 2021)
We report the case of a previously healthy young woman, who developed a severe form of COVID-19 with massive pneumonia and acute pericarditis in whom constrictive physiology developed rapidly. To our knowledge, this represents the second reported case of SARS-CoV-2 constrictive pericarditis, a rare, but severe cardiac complication.